Causal relationship between circulating insulin-like growth factor-1 and Parkinson’s disease: a two-sample Mendelian randomization study - Xu, Jiahao; Fan, Peidong; Yang, Jiacheng; Yin, Mingjuan; Wu, Jun; Chen, Chao; Ni, Jindong (Frontiers in Aging Neuroscience, 2024)
Background Linear associations between circulating insulin-like growth factor-1 (IGF-1) levels and Parkinson’s disease (PD) have been evidenced in observational studies. Yet, the causal relationship between IGF-1 levels and PD remains obscure. We conducted Mendelian randomization to examine the correlation between genetically predicted IGF-1 levels and PD. Methods By reviewing genome-wide association studies (GWAS) that are publicly accessible, we uncovered SNPs linked to both serum concentrations of IGF-1 and PD. A two-sample Mendelian randomization (MR) analysis was carried out to evaluate the individual effect of IGF-1 on PD. Results In a primary causal effects model in MR analysis, employing the inverse-variance weighted (IVW) method, IGF-1 levels exhibited a notable association with the risk of PD (OR, 1.020, 95% CI, 1.003–1.038, p = 0.0215). Multiple evaluations revealed that horizontal pleiotropy was improbable to distort the main results (MR-Egger: P PD intercept =0.719), and no bias was detected by leave-one-out analysis. Conclusion This study unearthed evidence indicating that heightened IGF-1 levels might be causally correlated with an increased risk of PD.